The Impact of Dividend Policy, Green Finance, and Profitability on Firm Value in the Energy and Infrastructure Sectors - Rini Mulyasari; Asep Risman (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2025)
This study aims to examine the effects of Green Finance, Dividend Policy, and Profitability on Firm Value in energy and infrastructure companies listed on the Indonesia Stock Exchange during the 2022–2024 period. A quantitative approach was employed using multiple linear regression analysis on 11 companies selected based on the availability of financial statements and sustainability reporting data. The findings indicate that a company's ability to generate profits makes a significant positive contribution to its market valuation, consistent with theoretical frameworks emphasizing financial performance and managerial signaling. These results support the view that management's efficiency in utilizing shareholders' equity enhances market confidence and increases firm value (Risman & Subhani, 2021). In contrast, Dividend per Share (DPS) and ESG Score were not found to have a significant effect on firm value. Although the bird-in-the-hand theory suggests that dividends serve as a positive signal to investors (Lintner, 1956), in capital-intensive sectors investors tend to place greater value on growth strategies driven by earnings reinvestment (Risman, 2021). Likewise, ESG Score has not yet become a primary determinant of investor decision-making, despite the widely recognized role of sustainability practices in strengthening risk management and enhancing long-term corporate reputation (Gustanto & Risman, 2025). This study recommends that companies continue to prioritize profitability improvement while strategically integrating green finance practices to create sustainable value. Furthermore, the findings provide opportunities for developing a more holistic firm valuation model by synergistically incorporating both financial and non-financial factors.